Rancang-bangun Alat Ukur Kadar Pati Ubi Kayu Menggunakan Loadcell dan Arduino Berdasarkan Metode Spesific Gravity - Prima Aprilliana; Amir Supriyanto; Arif Surtono (Jurnal Penelitian Sains, 2017)
It has been realized an instrument for measuring cassava starch content digitally based specific gravi-ty method. The instrument is designed using loadcell as mass sensor, Analog to Digital Converter (ADC) HX711, Arduino Uno as data processor, LCD, and personal computer. The principles of this instrument is us-ing specific gravity method, which are based on differences of cassava mass in the air and in the water. Cassa-va starch content calculated using Sungzikaw equation by microcontroller Arduino and displayed on LCD. The result showed that the instrument capable measure cassava starch content with maximum capacity of 2,2 kg and average error percentage of 1,4515%.